Factors Influencing Use of Monsoonsim Business Simulation by UTM Undergraduate Students - Shafudin, Mohd Yatim; Chin, Fei Goh; Raihanatul, Zahirah Mohamad (Macrothink Institute, 2018)
The study was conducted to investigate the factors that influenced the use of MonsoonSIM business simulation by the undergraduate students of Universiti Teknologi Malaysia (UTM). The objectives of this study were to evaluate the (i) relationship between perceived usefulness, perceived ease of use, and perceived enjoyment towards attitude to use MonsoonSIM, (ii) relationship between perceived usefulness, perceived enjoyment, and attitude to use towards the behavioral intention to use MonsoonSIM (iii) strongest determinants that influenced the students’ attitude to use MonsoonSIM. Two hundred and sixty UTM undergraduate students answered this e-questionnaire. Descriptive and inferential analyses were used to evaluate the data. The results of this study showed all the relationships were positively correlated, and that perceived enjoyment was the most significant factor influencing the students’ attitude to use MonsoonSIM. In conclusion, there is a higher possibility for the technology to be used by the users if it includes perceived usefulness, perceived ease of use, and perceived enjoyment.